Optimizing Poskestren for Reproductive Health Services for Adolescent Female Students at Al Fattah Islamic Boarding School Palembang - Dian Lestari; Ocktariyana Ocktariyana; Aprilina Aprilina (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Optimization is getting a state that gives the maximum value of a process or function. Poskestren are under the supervision of Puskesmas and function as health service posts in Islamic boarding schools providing health monitoring services for residents of Islamic boarding schools. The existence of health post-health cadres as peers who become guides in monitoring health and helping to monitor the health status of peers to be reported to a more authorized level. The young women of Al Fattah Islamic Boarding School are around 12 to 19 years old, living in a regular schedule set by the Islamic boarding school, often making them forget to pay attention to their health and reproductive health. In this community service, the team provides health check-up services and records the information needs needed by young women. This activity was carried out for 4 months and went smoothly. The result was that the knowledge and attitudes of young women towards reproductive health increased.